Investment Objectives of Sovereign Wealth Funds : A Shifting Paradigm - Petrova, Iva (IMF Working Papers; Working Paper ;, 2011)
While SWF investment objectives to some extent reflect inherent characteristics, notable differences in strategic asset allocation (SAA) exist even amongst SWFs of similar types. Even so, this paper shows that the global crisis may have changed SWF's asset allocations in ways that may not be ideal or justified in all cases and that a review of investment objectives may be warranted. It also argues for regular macro-risk assessments for the sovereign, the continued importance of SWFs as a stabilizer in international capital markets, as well as the active role they could play in international regulatory reform.